Hubungan Tingkat Pengetahuan dan Sikap terhadap Vaksin COVID-19 melalui Media Audiovisual pada Remaja - Sulistyna, Sulistyna; Munir, Zainal; Hafifah, Vivin Nur (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
COVID-19 vaccination is an essential measure to reduce virus transmission, decrease morbidity, and strengthen community immunity. Nevertheless, doubts remain among adolescents, influenced by their level of knowledge and attitudes toward the vaccine. This study aimed to analyze the relationship between knowledge and attitudes toward the COVID-19 vaccine through audiovisual media among adolescents at SMP Negeri 6 Probolinggo City. A quasi-experimental design with a pretest–posttest control group was employed, involving 50 respondents selected through total sampling, consisting of 25 students in the intervention group and 25 in the control group. Data were analyzed using the Wilcoxon test. The results indicated a significant difference in knowledge and attitudes in the intervention group before and after receiving audiovisual-based education (p < 0.05), while no meaningful change was observed in the control group. These findings highlight that audiovisual media is effective in improving adolescents’ knowledge and attitudes toward COVID-19 vaccination.